Tongxinluo (TXL), a Traditional Chinese Medicinal Compound, Improves Endothelial Function After Chronic Hypoxia Both In Vivo and In Vitro. Issue 6 (June 2015) - Zheng, Cui-Ying; Song, Li-Li; Wen, Jin-Kun; Li, Li-Min; Guo, Zong-Wei; Zhou, Pei-Pei; Wang, Chang; Li, Yong-Hui; Ma, Dong; Zheng, Bin
Abstract : Abstract: Vascular injury after chronic hypoxia leads to endothelial injury and structural damage to tight junctions (TJs), thereby resulting in a variety of cardiovascular diseases. Thus, attenuating hypoxia-induced damage has great significance for the prevention and treatment of cardiovascular disease. The aim of this study was to investigate whether the endothelial protection conferred by tongxinluo (TXL), a traditional Chinese medicinal compound, is related to its regulation of TJ protein expression. In vivo, we found that TXL could promote hypoxia-induced angiogenesis in lung and liver tissue. In vitro, we found that CoCl2 treatment significantly reduced the expression of the TJ proteins occludin, claudin-1, VE-cadherin, and beta-catenin in cultured human cardiac microvascular endothelial cells. TXL pretreatment abrogated the CoCl2 -induced downregulation of these TJ proteins. Conversely, overexpression of Krüppel-like factor 4 (KLF4) inhibited the expression of TJ proteins in human cardiac microvascular endothelial cells, an effect that was reversed by TXL pretreatment. Further experiments showed that TXL could promote endothelial cell proliferation by increasing KLF4 phosphorylation, thereby reversing the effect of KLF4 on the expression of TJ proteins. These findings provide a new molecular mechanism for the TXL-induced increase in TJ protein expression.